Analysis of the Effect of Environmental, Social and Governance (ESG) Disclosures on Capital Structure with Company Performance as an Intervening Variable (Empirical Study on Companies Listed in Sri-Kehati Index Stocks for the 2017-2019 Period) - Delvia, Shintya; Efni, Yulia; Haryetti, Haryetti (International Journal of Economic, Business & Applications, 2022)
This study aims to examine the effect of environmental, social, and corporate governance on capital structure with company performance as an intervening variable in companies listed in the sri-kehati index for the period 2017 – 2019. This study uses secondary data, namely on companies that are members of the Sri-Kehati index that disclose environmental, social and governance (ESG) scores on Bloomberg. The data used in this study with a total research sample of 54 data was determined by purposive sampling method.The results of this study indicate that environmental and governance has an effect on company performance while social has no effect on company performance. Environmental, social, and governance have no effect on capital structure. For indirect testing, the results show that environmental, social, and governance have no effect on capital structure through company performance as an intervening variable.